Practice under Psychological Pressure and Attention Focusing on the Learning Billiard Shot - Mahdiyeh Gharelar; Masumeh Shojaei; Hasan Mohammadzadeh (University of Tehran, 2019)
Psychological states affect focus of attention and play a mediating role in its effect on motor performance and learning. The present study investigated the effect of practice under psychological pressure and attention focusing with instruction on learning billiard shot. Participants were 48 female volunteer students (19-23 years old) who were randomly selected and assigned to 4 experimental groups (internal focus under high and low pressure, external focus under high and low pressure). The groups practiced for 8 sessions after the pretest. Acquisition test was performed in the last session of practice, and the retention test was conducted with 2 and 10 days of delay after the last practice session. The accuracy of the shots was scored according to the distance of the ball from the pit. The results of U Mann-Whitney test showed priority of internal attention in the acquisition and 10-day delay retention tests and priority of practice under low pressure in 10-day delay retention test (P<0.05). The results of Kruskal-Wallis test and pairwise comparisons indicated priority of the acquisition of internal attention under high pressure on external attention under high pressure and the priority of delayed retention of internal attention under low pressure on external attention under high pressure (P<0.05). It seems that given the nature of skill in terms of unchanged environmental conditions and high accuracy and attention requirements especially in the early stages of learning, practice under low psychological pressure conditions and internal focusing will result in more delayed retention for novice people